PERMASALAHAN DAN SOLUSI PERILAKU KEUANGAN MAHASISWA DI INDONESIA: STUDI DESKRIPTIF - Muhammad Rheza Tawakkal; Girang Permata Gusti; Rudi Triadi Yuliarto; Muhammad Zaini; Udin Rinaldi (Jurnal Ekonomi STIEP, 2023)
Students as the nation's generation of hope, who become the successors of leadership, must have good knowledge about how to apply the right patterns of financial behavior to daily life. The financial behavior of students will be seen when the process of entering money is received and the expenditure of money is carried out. The order of priority and percentage of the division of the financial management pattern will be well checked. In simple terms, when income is greater than expenses, this is the initial evidence of the right pattern of financial behavior. But if on the contrary, expenses are greater than income then this is a pattern of bad financial behavior. When passive income is successfully obtained through investment, this income will support active income and help to alleviate expenses that are routinely carried out at all times. This research uses a discriminatory method and a related literature study of student financial behavior. There are at least six problems and six solutions that can be provided to improve the financial behavior of students in Indonesia to be even better. The findings of this study are that students in Indonesia tend to 'ignore' the importance of learning about finances, and still have poor habits about how to put money so that it can be managed properly and more productively.